Epidemiological data and genome sequencing reveals that nosocomial transmission of SARS-CoV-2 is underestimated and mostly mediated by a small number of highly infectious individuals. Issue 4 (October 2021) - Lumley, Sheila F; Constantinides, Bede; Sanderson, Nicholas; Rodger, Gillian; Street, Teresa L; Swann, Jeremy; Chau, Kevin K; O'Donnell, Denise; Warren, Fiona; Hoosdally, Sarah; O'Donnell, Anne-Marie; Walker, Timothy M; et al.
Highlights: Current surveillance definitions underestimate SARS-CoV-2 nosocomial acquisition. Many cases of SARS-CoV-2 diagnosed within the first week of hospital admission were acquired in hospital. Whole genome sequencing revealed most nosocomial transmission occurs from a relatively limited number of highly infectious individuals. The majority of epidemiologically defined outbreaks consisted of multiple genomic introductions. Abstract: Objectives: Despite robust efforts, patients and staff acquire SARS-CoV-2 infection in hospitals. We investigated whether whole-genome sequencing enhanced the epidemiological investigation of healthcare-associated SARS-CoV-2 acquisition. Methods: From 17-November-2020 to 5-January-2021, 803 inpatients and 329 staff were diagnosed with SARS-CoV-2 infection at four Oxfordshire hospitals. We classified cases using epidemiological definitions, looked for a potential source for each nosocomial infection, and evaluated genomic evidence supporting transmission. Results: Using national epidemiological definitions, 109/803(14%) inpatient infections were classified as definite/probable nosocomial, 615(77%) as community-acquired and 79(10%) as indeterminate. There was strong epidemiological evidence to support definite/probable cases as nosocomial. Many indeterminate cases were likely infected in hospital: 53/79(67%) had a prior-negative PCR and 75(95%) contact with a potential source. 89/615(11% of all 803 patients) with apparent community-onset had a recent hospital exposure. Within 764 samples sequenced 607 genomic clusters were identified (>1 SNP distinct). Only 43/607(7%) clusters contained evidence of onward transmission (subsequent cases within ≤ 1 SNP). 20/21 epidemiologically-identified outbreaks contained multiple genomic introductions. Most (80%) nosocomial acquisition occurred in rapid super-spreading events in settings with a mix of COVID-19 and non-COVID-19 patients. Conclusions: Current surveillance definitions underestimate nosocomial acquisition. Most nosocomial transmission occurs from a relatively limited number of highly infectious individuals.